Funkcjonowanie samorządów pracowniczych w wybranych krajach realnego socjalizmu - Wdzięczak, Janusz (Annales. Etyka w Życiu Gospodarczym, 2016)
The aim of the article is to present the attempts of establishing institutions of a systemof worker’s self-management in the selected countries of the so-called real socialismsystem in Eastern Europe. The analysis considers three of those countries,namely Yugoslavia, Poland and Hungary, whose experiences in participation of theemployees’ implementation were the most significant. Particular attention was paidto the evolution of socialist regimes approach to workers’ self-management. Thepaper tries to answer the question whether workers’ self-management posed a threatto the socialist regimes persistence. The research method used in the study is an indepthsurvey and analysis of literature and legal acts.